DEKONSTRUKSI SEJARAH PERANG KERAJAAN-KERAJAAN ISLAM DI ASIA TENGGARA DALAM PEDAGOGI SEJARAH - Supriatna, Nana (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2008)
In this article, subject-matter of history at the junior and senior high schools as well (SMP and SMA) on Islamic Sultanates in the Nusantara region â€œis deconstructedâ€ from the â€œhistory of warsâ€ to become Islamic history which is now relevant to the contemporary social issues faced by the Muslim ummah in Indonesia. Common issues such as poverty, ummah enforcement, working ethos, entrepreneurship, social networking (silaturahim) and the commemoration of the glorious grandeur of the past maritime world of the Sultanates, are all historic issues which are still problems faced by the Muslim ummah and, are more interesting as foci of inquiry in the learning process of history class. Deconstruction of war history in history pedagogy is necessary and in accordance with contextual approach and, at the same time as a response to the accusation that Islam is identical with violence and terrorism. Deconstruction in history pedagogy is to build a new image on Islamic history which. It is very important for the Islamic ummah to response all kinds of challenges which they confront at this time. In this article the notion of deconstruction is carried out on conventional history which stresses too much on progress account experienced by the Sultanates in the Nusantara, including wars which becomes problematic topic and contextual with the real life of the students. The results of deconstruction will be constructed by using interrelated construction of topics, concepts, emancipator questions, and associate to contemporary social problems which are faced by the Muslims.